Superalloys 2008 (Eleventh International Symposium) 2008
DOI: 10.7449/2008/superalloys_2008_91_97
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ruthenium on Microstructure and Stress Rupture Properties of a Single Crystal Nickel-Base Superalloy

Abstract: The effect of Ru on microstructure and stress rupture properties of an advanced Ni base single crystal alloy has been investigated. The experimental results showed that the addition of 4 wt.% Ru had hardly effect on the phase precipitation behavior of as-cast alloy, i. e., the microstructure is composed of γ and γ' phases for both Ru free and Ru containing alloys. However, under the heat treatments of 1305℃-1315 /16h ℃ solutioning and 1140℃/4h+ 870 /20h ℃ aging, and the thermal exposure under 1100 /1000h, ℃ th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…[31][32][33][34][35] Fig. 3 also illustrates that the interpretation of the significance of observed results varies in the literature; for example, Han et al 30 concluded that there was evidence for reverse partitioning on addition of 1.49 at.% Ru to their alloy, whereas Reed et al 31 concluded that there was no evidence on addition of 1.26 at.% Ru to a different alloy. This is reflected by the relative behaviour of the Al partitioning ratios but, when considering γ-partitioning elements, the relative change in the W and Re ratios suggests that the former are ascribing greater significance to a similar magnitude of change than the latter.…”
Section: Comentioning
confidence: 96%
See 1 more Smart Citation
“…[31][32][33][34][35] Fig. 3 also illustrates that the interpretation of the significance of observed results varies in the literature; for example, Han et al 30 concluded that there was evidence for reverse partitioning on addition of 1.49 at.% Ru to their alloy, whereas Reed et al 31 concluded that there was no evidence on addition of 1.26 at.% Ru to a different alloy. This is reflected by the relative behaviour of the Al partitioning ratios but, when considering γ-partitioning elements, the relative change in the W and Re ratios suggests that the former are ascribing greater significance to a similar magnitude of change than the latter.…”
Section: Comentioning
confidence: 96%
“…This is reflected by the relative behaviour of the Al partitioning ratios but, when considering γ-partitioning elements, the relative change in the W and Re ratios suggests that the former are ascribing greater significance to a similar magnitude of change than the latter. It is worth considering also the variation in techniques used to measure the compositions in each of these investigations, from inductively-coupled plasma spectroscopy after extraction of the γʹ 30 to atom probe tomography 31 . The different levels of accuracy inherent in these techniques may explain some of the variation displayed in Fig.…”
Section: Comentioning
confidence: 99%
“…On the other hand, this can be inhibited due to good interfacial strength towards the matrix or a γ'-film enclosing µ-phase particles (Simonetti and Caron, 1998;Wang et al, 2010;Yang et al, 2006). During creep of γγ'-superalloys, μ and other TCP phase precipitates have been observed to accelerate rafting (Zhao and Dong, 2012) and to distort the unrafted (Pyczak et al, 2000;Yang et al, 2007) and, more severely, rafted microstructures (Han et al, 2008;le Graverend et al, 2011;Moverare et al, 2009;Simonetti and Caron, 1998;Sugui et al, 2010). However, while in most studies the µ-phase precipitates are assumed not to deform themselves, ductility of needle shaped precipitates has indeed been found (Qin et al, 2009;Yang et al, 2006) and no detrimental effect on the tensile strength was found during high temperature tensile testing (Chen et al, 1980;Tawancy, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly the mechanisms by which µ-phase precipitates affect creep at high temperatures are still under discussion (Cheng et al, 2011;Epishin et al, 2010;Han et al, 2008;He et al, 2005;Moverare et al, 2009;Simonetti and Caron, 1998;Sugui et al, 2010;Volek and Singer, 2004;Wang et al, 2010;Yang et al, 2006). Le Graverend et al (le Graverend et al, 2011) have conducted FEM calculations of nickel-based superalloys considering plasticity of µ-phase precipitates at higher temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…However, Walston et al supported the "reverse partitioning" theory by studying lowCr-containing (2wt.%) and Ru-containing (0~6wt.%) superalloys [14]. Ofori et al [15] and Han et al [16] proved the "reverse partitioning effect" of high level of Ru content in the non-Cr-containing and in the low-Cr-containing superalloys. Ru has a tendency to partition into g matrix and has a strong preference to occupy Al sites.…”
Section: Reverse Partitioningmentioning
confidence: 93%